SIGNIFICANCE AND GENO-/SEROTYPIC CHARACTERISTICS OF STREPTOCOCCUS PNEUMONIAE IN THE PATHOGENESIS OF EXACERBATIONS OF CHRONIC OBSTRUCTIVE RESPIRATORY DISEASES - Nalibaeva R.A.; Liverko I.V. (Central Asian Journal of Medicine, 2025)
Pneumococcal infection caused by Streptococcus pneumoniae remains one of the leading causes of infectious morbidity and mortality worldwide, particularly among individuals with chronic respiratory diseases. According to the World Health Organization (WHO), more than 1.6 million deaths are recorded annually due to invasive forms of pneumococcal disease, with the highest vulnerability observed in elderly patients and individuals with comorbid conditions. Chronic obstructive pulmonary diseases (COPD) significantly increase the risk of bacterial colonization and the development of severe complications associated with S. pneumoniae. The present study aims to investigate the frequency of pneumococcal detection and to analyze its serotypic and phenotypic distribution among patients with COPD, in order to assess the local serotype landscape and to inform potential adjustments in vaccination strategies.